The Effect of N-Nitrosodimethylamine on Enzyme Activities and Histology in the Mouse - Salleh, Mohd Nazil (1999)
This thesis studied the effects of acute, sub-chronic and chronic exposures of NDMA on the enzyme activities of five tumour markers namely: glutathione Stransferase (GST), gamma glutamyl transpeptidase (y-GT), glutathione peroxidase (GSH-Px), glutathione reductase (GSH-R) and uridyl diphosphoglucuronyl transferase (UDPGT) in the liver and kidney of male mice were. Forty-eight male mice ICR strain, Mus musculus (26-3 8g, 8 weeks old) were divided into four groups. A single batch consisted of 12 mice; one-half of them for enzyme activities and the other one-half for histological study. Acute group (n= 12) were injected with a single dose of 0.5 mg/kg b.w. of NDMA. Sub-chronic group received 0.25 mg/kg b.w. of NDMA with twice i.p. injection over a one month period. Chronic group (n= 12) were injected with 0.05 mg/kg b.w. of NDMA given four times over a period of four month. The mice were sacrificed by cervical dislocation after treatment. In the liver, acute, sub-chronic and chronic exposure to NDMA showed increased enzyme activities (GST, GSH-R, GSH-Px, y-GT and UDPGT: except y-GT at acute exposure) in comparison with control groups (P<0.05). In the kidney, however the effect of NDMA exposure was rather inconsistent. All the enzyme activities increased in the acute exposure. Meanwhile, in the sub-chronic and chronic exposure some enzyme activities increased (e.g.: GST, y-GT and UDPGT) and some enzyme activities (e.g.: GSH-R) did not change significantly. Administration of NDMA to mice by intraperitoneal inj ection over various periods of times to a total of 0.05- 0.5 mg/kg body weight caused the development of the tumour in the liver and kidney. Single acute dose (0.5 mg/kg b.w. of NDMA) produced anaplastic tumour and tubular degeneration in the kidney. Prolonged exposure (chronic) of mice to NDMA produced a high incidence of hepatocellular adenoma and also necrosis in the liver. This study demonstrated that there is a very strong correlation between enzyme activities and cell damage. Therefore, it can be concluded that some enzyme activities especially GST, y-GT and UDPGT can be used as tumour markers.